Zakat management system at UiTM Seremban: analysis of zakat distribution strategies through e-Zakat System / Ahmad Faiz Yaakob … [et al.] - Yaakob, Ahmad Faiz; Mohd Yunus, Zulhilmi; Mat Salleh, Mohd Kamel; Mohd Azli, Rafidah (Center for Islamic Philantrophy & Social Finance (CIPSF), 2024)
The complaints and dissatisfaction of some zakat recipients towards the delivery system in Malaysia is common but should not be taken lightly. Specifically, at UiTM Seremban, the frequent delay in the distribution of aid is one of the issues that are often associated among a few zakat recipients. Research on zakat in Malaysia especially in terms of the zakat delivery system which specifically examines and dives into the views and feelings of recipients towards the zakat delivery system is very limited. This gap actually prevents appropriate interventions to coordinate the process of delivering zakat more effectively. The use of the framework by Schwartz (1976) is seen to offer room for improvement of the existing zakat delivery system that looks from the point of view of those who receive and enjoy the aid. A study based on semi-structured interviews among zakat recipients obtained through purposive sampling techniques has addressed several weaknesses that exist in the delivery process, including disbursement delays, and the dissemination of information that is not widespread. Among the recommendations obtained is the recognition of informal channels (i.e., WhatsApp) as an effective information dissemination channel and increase students' self-sufficiency in managing finances independently.